A Study of Implementation and Success of Building Bye-Laws in Lahore - Sherwani, Rummana; Hashmi, Arsala; Khan, Faiqa (Annals of Human and Social Sciences, 2024)
Building Regulations plays significant role in shaping the cities around the globe. The proper implementation and interpretation of these regulations in different parts of the world shaped some of the beautiful cities like Amsterdam and Copenhagen. The uncontrolled growth due to the ineffective planning rules and regulations in third world countries like Pakistan resulted into haphazard city planning. This research is focused on the identification of such factors that includes mainly social, economic and institutional in addition to the interpretations an implementation issues. The methodology adopted comprised of literature review followed by questionnaire surveys along with the socioeconomic and institutional studies. The data was further analyzed by SPSS to compile the results. The data concluded that public participation is mandatory for the effective enforcement of the building bye-laws. This research conclude with the recommendation strategy for proper implementation and interpretation of the Building Regulations for successful planning of the cities like Lahore in Pakistan.